2007
DOI: 10.1590/s1415-790x2007000400005
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of multiple sclerosis in the city of Santos, SP

Abstract: OBJECTIVE: To assess the prevalence of multiple sclerosis (MS) in the city of Santos, SP. METHOD: Evaluation of data from the Reference Center for MS of the coastal region of the State of São Paulo, from the Regional Association of Patients with MS (APEMBS), with active participation of all neurologists and neurosurgeons of the city, data from IBGE, from the city council, and from EMPLASA. The protocol proposed by the BCTRIMS (already used in other similar studies) was used for data collection and analysis, Ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 9 publications
0
16
0
4
Order By: Relevance
“…The prevalence of MS in north-eastern regions of Brazil is estimated at 5%, and 15% to 18% within the south-south eastern regions (CARDOSO et al, 2006). Most studies have demonstrated that females are more predisposed to MS than males, with predominance of cases in patients of Caucasian relative to African descent (ARRUDA et al, 2001;CARDOSO et al, 2006;FRAGOSO;PERES, 2007;FINKELSZTEJN et al, 2009). Although, it has been established that immigrants from areas of elevated risk for MS who have migrated, before 16 years-of-age, to a low-risk geographical location are likely to maintain their risk-factor (DEAN et al, 1976), this phenomenon was not investigated in the epidemiological studies analysed considering the impact of European immigration on the development of Brazil.…”
Section: Public Health Concernsmentioning
confidence: 99%
“…The prevalence of MS in north-eastern regions of Brazil is estimated at 5%, and 15% to 18% within the south-south eastern regions (CARDOSO et al, 2006). Most studies have demonstrated that females are more predisposed to MS than males, with predominance of cases in patients of Caucasian relative to African descent (ARRUDA et al, 2001;CARDOSO et al, 2006;FRAGOSO;PERES, 2007;FINKELSZTEJN et al, 2009). Although, it has been established that immigrants from areas of elevated risk for MS who have migrated, before 16 years-of-age, to a low-risk geographical location are likely to maintain their risk-factor (DEAN et al, 1976), this phenomenon was not investigated in the epidemiological studies analysed considering the impact of European immigration on the development of Brazil.…”
Section: Public Health Concernsmentioning
confidence: 99%
“…In Brazil, although the distribu on of cases of MS is not well known, studies on its manifesta on in the ci es of São Paulo and Santos revealed rates of 15 cases per 100,000 popula on (3)(4) .…”
Section: Introductionmentioning
confidence: 99%
“…Its population consists of 723,515 inhabitants 13 , in an area of 211 475 km². Much of the city is situated on low-lying coastal plains, with an approximate elevation of 20 meters above the sea.…”
mentioning
confidence: 99%
“…The black population had less presence in the formation of Paraíba population when compared to other states in the Northeast 15,16 . According to the last census conducted by IBGE in 2010, from an ethnic-racial point-of-view, Paraíba has a population with a prevalence of mixed races (52.3%), followed by whites (42.6%), blacks (3.9%) and, finally, indigenous and yellows (0.36%), and those with no racial statement (0.79%) 13 . The aim of this study is to describe the clinical and epidemiological characteristics of patients diagnosed with MS living in the city of João Pessoa, Paraíba, Brazil.…”
mentioning
confidence: 99%